Unravelling the evolutionary trajectory: Exploring the dynamics of oilseeds cultivation in Haryana 1989-90 to 2020-21: UNRAVELLING EVOLUTIONARY TRAJECTORY: EXPLORING DYNAMICS OF OILSEEDS CULTIVATION - SHIVJEET KAUR; SUKRITI SHARMA (Journal of Oilseeds Research, 2024)
The performance of all oilseeds in Haryana is examined in the current research utilizing time series data gathered from 1989-1990 to 2020-2021 from various sources. After reviewing the performance of oilseeds, it was determined that the yield aspect of all oilseeds at the national level had demonstrated notable performance. Over the course of the study period, there was a slow but significant increase in the area, output, and yield of all oilseeds. Oilseed supply and demand in the country are out of balance, forcing us to import edible oils. To close the gap between oilseed production and consumption, the government must implement technological advances and increase oilseed output. The various climatic conditions of Haryana provide ideal habitats for the development of oilseeds throughout each of its districts. The state has a predominately dry climate with warm summers and rather chilly winters. Oilseed crops including mustard, sunflower, and soybean are particularly well-suited to these circumstances. The state’s winter environment is well-aligned with the rabi season, which runs from November to April. This creates an optimal window for the growth of oilseeds. The comparatively low levels of humidity during this time aid in the prevention of fungi diseases and encourage strong plant growth. The loamy and sandy-loam soils of Haryana also aid in the success of oilseeds by promoting root growth and good drainage.